Spc98p and Spc97p of the yeast γ‐tubulin complex mediate binding to the spindle pole body via their interaction with Spc110p - Knop, Michael; Schiebel, Elmar (The EMBO journal, 1997)
Previously, we have shown that the yeast γ‐tubulin, Tub4p, forms a 6S complex with the spindle pole body components Spc98p and Spc97p. In this paper we report the purification of the Tub4p complex. It contained one molecule of Spc98p and Spc97p, and two or more molecules of Tub4p, but no other protein. We addressed how the Tub4p complex binds to the yeast microtubule organizing center, the spindle pole body (SPB). Genetic and biochemical data indicate that Spc98p and Spc97p of the Tub4p complex bind to the N‐terminal domain of the SPB component Spc110p. Finally, we isolated a complex containing Spc110p, Spc42p, calmodulin and a 35 kDa protein, suggesting that these four proteins interact in the SPB. We discuss in a model, how the N‐terminus of Spc110p anchors the Tub4p complex to the SPB and how Spc110p itself is embedded in the SPB.